2022
DOI: 10.1093/conphys/coac006
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm and invertebrate consumption by western sandpipers (Calidris mauri) and dunlin (Calidris alpina)during spring migratory stopover: insights from tissue and breath CO2 isotopic (δ13C,δ15N) analyses

Abstract: Shorebirds use key migratory stopover habitats in spring and fall where body proteins are replenished and lipids stored as fuel for the remaining journey. The Fraser River estuary, British Columbia, Canada, is a critical spring stopover site for hundreds of thousands of migrating western sandpiper, Calidris mauri, and dunlin, Calidris alpina. Intertidal biofilm in spring is an important nutritional source for western sandpiper, with previous isotopic research predicting 45–59% of total diet and 50% of total en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Invertebrates can constitute a large fraction (~ 20-50%) of the diets of western sandpipers and dunlin (Kuwae et al 2008;Jardine et al 2015;Hobson et al 2022), and their abundance, biomass, and diversity might explain the observed differences in shorebird counts between Brunswick Point and Iona Foreshore. Shorebird distribution and abundance has been related to the abundance of benthic invertebrates (Colwell and Landrum 1993) but not always (Horn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invertebrates can constitute a large fraction (~ 20-50%) of the diets of western sandpipers and dunlin (Kuwae et al 2008;Jardine et al 2015;Hobson et al 2022), and their abundance, biomass, and diversity might explain the observed differences in shorebird counts between Brunswick Point and Iona Foreshore. Shorebird distribution and abundance has been related to the abundance of benthic invertebrates (Colwell and Landrum 1993) but not always (Horn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Smallbodied shorebirds consume a variety of prey, including marine invertebrates and intertidal biofilm, a thin layer of microalgae, bacteria, and other microorganisms embedded in a mucilaginous matrix composed of extracellular polymeric substances (EPS; Decho 2000;Stal 2010). Intertidal biofilm can account for 45-59% of the shorebird total diet or 50% of their daily energy budget (Kuwae et al 2012;Hobson et al 2022). On the Fraser River Estuary, British Columbia, Canada, Jardine et al (2015) investigated biofilm consumption by Western Sandpiper Calidris mauri and found that sites with the highest proportion of intertidal biofilm in the diet supported larger numbers of birds, suggesting that site use was related to biofilm consumption.…”
Section: Introductionmentioning
confidence: 99%